Effect of Carum carvi essential oil on ERG6 gene expression and virulence factors in Candida albicans - Samira Nasiri; Masoomeh Shams-Ghahfarokhi; Mehdi Razzaghi-Abyaneh (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: The present study was conducted to investigate the inhibitory effects of Carum carvi essential oil (EO) against ERG6 gene expression in relation to fungal growth and some important virulence factors in Candida albicans. Materials and Methods: The minimum inhibitory concentration (MIC) of C. carvi EO against C. albicans was determined by the Clinical and Laboratory Standards Institute M27-A4 method at a concentration range of 20-1280 μg/ml. Furthermore, the expression of ERG6 gene was studied at the 0.5× MIC concentration of C. carvi EO using real-time polymerase chain reaction. The proteinase and phospholipase activities, cell surface hydrophobicity (CSH), and cell membrane ergosterol (CME) content of C. albicans were also assessed at the 0.5× MIC concentration of the plant EO using the approved methods. In addition, fluconazole (FLC) was used as a control antifungal drug. Results: The results indicated that the MIC and minimum fungicidal concentration of C. carvi EO for C. albicans growth were 320 and 640 μg/ml, respectively. The expression of fungal ERG6 at an mRNA level and ergosterol content of yeast cells were significantly decreased by both C. carvi EO (640 μg/ml) and FLC (2 μg/ml). The proteinase and phospholipase activities were also reduced in C. carvi EO by 49.82% and 53.26%, respectively, while they were inhibited in FLC-treated cultures by 27.72% and 34.67%, respectively. Furthermore, the CSH was inhibited in EO- and FLC-treated cultures by 12.75% and 20.80%, respectively. Conclusion: Our findings revealed that C. carvi EO can be considered a potential natural compound in the development of an efficient antifungal agent against C. albicans.